MICROSTRUCTURE OF THYROID GLAND IN QUAIL - Suryawanshi, R D; Ladukar, Neeta; Shankhpal, V D; Ladukar , O N; Narkhede, H P; Shirsikar, P M (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Thyroid glands from 15 Japanese quails, ranging from 1 week to 9 weeks, were collected. The thyroid follicles were separated from each other by collagen fibers. The small and medium were abundant as compared to large follicles. These follicles were categorized as active and inactive on the basis of the type of epithelium and nature of colloid substance. Inactive follicles were more in adult quails. Large parafollicular cells were observed in intra-follicular space.
Keywords: Histology; Thyroid gland; Japanese quail